2014
DOI: 10.5586/aa.2014.034
|View full text |Cite
|
Sign up to set email alerts
|

The growth and flowering of Hyacinthus orientalis L. Forced in pots under fluorescent light of different colours

Abstract: Three hyacinth cultivars were forced under fluorescent lamps which emitted white, blue, green, yellow and red light. The plants started flowering in the first decade of February. The forcing period for two cultivars, ‘Anna Marie’ and ‘Blue Star’, was shortest under lamps emitting red light. The cultivar ‘White Pearl’ flowered equally early under lamps emitting red, white and blue light. The impact of light colour (wavelength) on the leaf greenness index (SPAD) was demonstrated. The photosynthetic activity of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…Bailey (1963) stated that the length of hyacinth leaves is 20-30 cm and leaf width is 1.25-3.75 cm. Smigielska et al (2014) reported that leaf lengths ranged between 24.30 and 28.40 cm. The average leaf length was the same with the finding.…”
Section: Discussionmentioning
confidence: 99%
“…Bailey (1963) stated that the length of hyacinth leaves is 20-30 cm and leaf width is 1.25-3.75 cm. Smigielska et al (2014) reported that leaf lengths ranged between 24.30 and 28.40 cm. The average leaf length was the same with the finding.…”
Section: Discussionmentioning
confidence: 99%
“…The number of leaves in the plants treated with the NPK fertilizer was 5-7 leaves, which was compared to control and other treatments. The lower number of leaves in Hyancith may belong to the efficiency of the photosynthesis process with white and yellow light playing an important role in the flower growth and blooming process and, thus, the dates of bulb production (Smigielska et al, 2014) 3.2.4. Flower Length (cm): There were no significant differences in flower length among the plants treated with different fertilizers.…”
Section: Number Of Leavesmentioning
confidence: 99%
“…They emit different colors-such as blue, violet, pink, white and yellow-if they are placed under fluorescent lamps (Dole and Wilkins, 2005). The flowers usually first bloom in February (Smigielska et al, 2014). It is native to the Mediterranean region and South Africa (Hu et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…The swollen portion consists mostly of fleshy, food storing scales attached to a short flat stem. The plants start flowering in the first part of February (Smigielska et al, 2014). The plant prefers moist but light sandy to loamy soils.…”
Section: Introductionmentioning
confidence: 99%